Responsabilidad social municipal y gestión del talento humano en gobiernos locales de Tarma, Perú - Medrano Osorio, Gabriel P. (2024)
Objective. The research was objective general to determine the relationship existent between internal social responsibility (ISR) and human talent management (HTM) in the municipalities of the province of Tarma, department of Junin, Peru. Materials and methods. The research was of approach quantitative, basic type, level explanatory, and non-experimental design. The population was confirmed for all the collaborators named and hired from six district municipalities of the province of Tarma, Junin region. The sampling was non-probabilistic of census type. The technique used for the collection of data was the survey and the instruments were a questionnaire by the management of the talent human with 59 items and a questionnaire about internal social responsibility in the municipality. To measure the correlation, was applied the rho of Spearman's. Results. The main results demonstrate that there's a correlation positive low between the ISR and the THM in the municipalities of the province of Tarma; results support the general hypothesis, indicating a low positive correlation (value rs = 0.264) between both study variables. Conclusions. The relationship between ISR and HTM in the municipalities of the province of Tarma is low, which is manifested in the high rate of collaborators turnover and the presence of labor-related illnesses (stress and burnout syndrome).